Synthesis and Characterization of Some Mixed Ligand Complexes of Thorium(IV) and ioxouranium(VI) with 1-Carbamido-3-Methylpyrazol-5-One and Various Anions - Rajendran, G. (Asian Journal of Chemistry, 2010)
A series of 10 mixed ligand complexes of two actinide metal ions, viz., Th(IV) and UO2(VI) with 1-carbamido-3-methylpyrazol-5-one (CMP) and various anions such as nitrate, acetate, thiocyanate, oxalate and sulphate have been synthesised and characterized on the basis of elemental analysis, molecular mass, molar conductance, IR spectra, TG and DTG data. These complexes have the general formulae [(Th(CMP)2(a)4)], [(Th(CMP)2(aa)2)], [(UO2(CMP)2(a)2)] and [(UO2(CMP)2(aa))], where a = monovalent anions such as acetate, nitrate and thiocyanate and aa = divalent anions such as oxalate and sulphate. In these complexes, CMP acts as a neutral bidentate ligand, the anions such as acetate, nitrate and thiocyanate act as monovalent unidentate ligands, and the anions such as oxalate and sulphate act as divalent bidentate ligands.